7 Lived experiences of end-of-life care at home in the UK: a scoping literature review. (14th March 2023) - Clark, Claire; Fenning, Stephen; Bowden, Jo
Abstract : Background: Home is the preferred place of care and death for most people with advanced illness and the proportion of people dying at home has risen sharply during the COVID-19 pandemic. However, little is known about the reality of end-of-life care in this setting for patients, their families and unpaid carers. We aimed to examine the published literature on these lived experiences. Methods: A scoping review was undertaken in accordance with the PRISMA-ScR checklist. All primary qualitative research papers published in the English language between 2010 and 2022 and exploring the lived experience of patients, families and/or unpaid carers in the United Kingdom were eligible for inclusion. The online databases CINAHL and MEDLINE were searched with relevant MeSH terms and keywords. Results: In total, 462 papers were screened, 58 underwent full text review and 13 studies were retained in the final set. All studies explored the experience of bereaved family and/or carers and only one study interviewed a dying patient. Where specified, the majority of experiences related to deaths from cancer, many with specialist palliative team involvement. No studies considered end-of-life care at home during the COVID-19 pandemic. The included papers yielded a breadth of diverse findings but the most common subject themes related to the availability and quality of care and support for families and carers. Conclusion: Currently, there is limited published evidence exploring the lived experience of those receiving and supporting end-of-life care at home. More research is needed to examine the first-hand experience of patients and to understand better the reality of deaths at home due to non-cancer conditions and where specialist palliative care services are not involved.